A Multiplex PCR-Based Next Generation Sequencing-Panel to Identify Mutations for Targeted Therapy in Breast Cancer Circulating Tumor Cells - André Franken; Mahdi Rivandi; Liwen Yang; Bernadette Jäger; Natalia Krawczyk; Ellen Honisch; Dieter Niederacher; Tanja Fehm; Hans Neubauer (Applied Sciences, 2020)
Targeted therapy has become the preferred approach to treat most cancers, including metastatic breast cancer. Using liquid biopsies, which can act as a dynamic diagnostic tool, is an appealing concept to identify effective therapies. In order to identify mutations from circulating tumor cells (CTCs) on single cell level, we have developed a multiplex PCR-based next generation sequencing-panel. The CTCs were enriched using the CellSearch system and isolated by micromanipulation followed by whole genome amplification of their DNA. Afterwards, mutation hotspot regions in the PIK3CA, the ESR1, the AKT1, and the ERBB2 genes were amplified and barcoded. Sequencing was performed on a MiSeq system. The assay was validated with cells from various cell lines displaying the expected mutations. Mutations that provide the basis for potential targeted therapies were detected in 10 out of 13 patients in all analyzed genes. In four patients, mutations in more than one gene were observed—either in the same cell or in different cells, suggesting the presence of different tumor cell clones, which might be targeted with combination therapies. This assay is a time and cost effective tool to investigate the most relevant genomic positions indicative for targeted therapies in metastatic breast cancer. It can support therapy decision to improve the treatment of cancer patients.